Integrasi Kesepakatan Mediasi dalam Amar Putusan Perceraian (Studi Putusan Nomor 2145/Pdt.G/2022/PA.Ckr) - Alysia Hapsari, Leilani; Safrilia Seta Wibawa , Kinanti; Septiningsih, Ismawati (Universitas Jambi, Fakultas Hukum, 2026)
This article discusses the implementation of agreements between parties in divorce cases through a case study of the Cikarang Religious Court Decision Number 2145/Pdt.G/2022/PA.Ckr. This study aims to analyze how mediation agreements can be used as a basis for court decisions by a panel of judges. The research method used is normative juridical with a case study approach. The results of the discussion show that the judges not only recognized the mediation agreement as a legal fact, but also integrated its entire substance into the verdict to ensure justice and legal protection, especially for children. The verdict shows that the results of mediation as outlined in the lawsuit and ratified in the verdict have permanent legal force and can be executed without the need for a new lawsuit. These findings emphasize the importance of mediation as an effective and responsive instrument for resolving family disputes.